SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SERUM AVOSKIN YANG SESUAI DENGAN KEBUTUHAN KULIT WAJAH MENGGUNAKAN LOGIKA FUZZY - Dite Arum salsabila; Ulinnuha Nurannisa', Ramdhan Alamsyah Putra, Adi Suwondo (ADISAM PUBLISHER, 2023)
This research aims to develop a fuzzy logic-based Decision Support System in choosing Avoskin serum that suits the needs of facial skin. The use of fuzzy logic helps overcome uncertainty and complexity in decision making. This research is a new scientific contribution in the application of fuzzy logic to the selection of skin care products and is expected to provide practical benefits for individuals in choosing products that suit their skin needs. The research method includes the creation of fuzzy membership functions and the formation of fuzzy rules based on the knowledge of beauticians and dermatologists. The results show that this decision support system is able to provide more personalized and accurate serum recommendations, by overcoming uncertainty and complexity in decision making. The inference and defuzzification processes successfully produce consistent and relevant recommendations according to different facial skin data. In conclusion, the application of fuzzy logic in Avoskin serum selection decision support system is effective in providing recommendations that suit the user's facial skin needs.This method has the potential to improve the effectiveness and efficiency of skin care, making a positive contribution to the beauty care industry. Further research is needed to extend the validity and involve more diverse facial skin data to improve the quality and generalization of this system in providing more precise and relevant recommendations for users.